Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Produk di Larissa Aesthetic Center Pasific Mall Tegal - Kusumaningati, Iip Dyah; Pujiastuti, Endah; Zahira Kirana (PT. Karya Inovatif Nusantara, 2024)
Currently, the beauty industry is growing rapidly. This result in more competitors and product choices for consumers. Sales transaction data for Larissa Aesthetic Center Pasific Mall Tegal products in 2022 experienced fluctuations. The purpose of this study was to determine the effect of marketing mix on product purchasing decisions at Larissa Aesthetic Center Pasific Mall Tegal. This type of research is quantitative. The data collection method was carried out by distributing questionnaires, interviews and documentation. The population in this study were 1.938 people who were the average monthly consumers who bought products and the sample in this study were 96 respondents. The data analysis technique was carried out by multiple linear regression. The result showed that: (1) product has a significant effect on product purchasing decisions with a significant value of 0,000<0,05; (2) price has a significant effect on product purchasing decisions with a significant value of 0,010<0,05; (3) place has no significant effect on product purchasing decisions with a significant value of 0,391>0,05; (4) promotion has a significant effect on product purchasing decisions with a significant value of 0,000<0,05; and (5) product, price, place and promotion simultaneously has a significant effect on product purchasing decisions with a significant value of 0,000<005. The magnitude of the influence of marketing mix on purchasing decisions is indicated by the R Square value of 71,7%.